ANALYSIS OF READINESS IN TEACHING ENGLISH CLASS AT SMAN 8 PINRANG - Wahyudi Wahyudi; Muh Firmansyah JN; Ahmed Sardi; Adi Isma (Journal of English Education, 2025)
The purpose of the research is to find out how prepared teachers are in teaching english in their main classes at SMAN 8 Pinrang. This research uses a descriptive qualitative method with the population in this research being English teachers at SMAN 8 Pinrang. The samplingthecniqueused total sampling, so that a sample of 4 English teachers at SMAN 8 Pinrang was obtained. The data collection technique used in this research was interviews and checklist observation. Interview analysis research shows that English teachers have quite good preparedness, and this is proven by how they can overcome problems during the teaching and learning process in class. Such as when students just sit quietly without any initiative to participate actively in the learning process, the teacher chooses a reward method and punishment to induce students to be more active in the learning process.